2016
DOI: 10.18805/lr.v0iof.9292
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of feed value of alfalfa (Medicago sativa L.) harvested at different maturity stages

Abstract: The aim of this study was to determine the green herbage and dry herbage yield, chemical and nutritional values and RFV of alfalfa (Medicago sativa L.) at different stages of maturity under Isparta ecological conditions in 2012. To achieve this goal random sampling plots was created according to an experimentation pattern, and the number of harvests was determined according to regional conditions. In chemical analysis, the following samples were analyzed for Dry Matter (DM), Crude Protein (CP), Ether Extract (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
4
27
0
Order By: Relevance
“…The lower mean CP content in 2008 could be due to slightly more mature plants at harvesting time than those in the 2009. CP concentration values determined in the present study are lower than those reported by Kallenbach et al, (2002);Spandl and Hesterman (1997);and Al-Ghumaiz (2012), while they were similar with those reported by Canbolat et al (2006);and Avci et al (2007); and Karayilanli and Ayhan (2016).…”
Section: Crude Protein Contentsupporting
confidence: 90%
“…The lower mean CP content in 2008 could be due to slightly more mature plants at harvesting time than those in the 2009. CP concentration values determined in the present study are lower than those reported by Kallenbach et al, (2002);Spandl and Hesterman (1997);and Al-Ghumaiz (2012), while they were similar with those reported by Canbolat et al (2006);and Avci et al (2007); and Karayilanli and Ayhan (2016).…”
Section: Crude Protein Contentsupporting
confidence: 90%
“…It is valuable for livestock feeding, biofuel and environmental balance (perenniality, soil improvement and no requirement for nitrogen fertilizer) (Flajoulot et al, 2005;Cerasela et al, 2010;Karayilanli and Ayhan, 2016). Therefore, it is important to study and protect the alfalfa germplasm of the United States.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a significant increase in RFV value was observed in seeds of Atlanta cultivar only after double application of the biostimulant at 1.0% concentration. RFV studies are primarily conducted for roughage (Kusvuran, et al, 2014;Karayilanli and Ayhan, 2016), yet to balance the entire feed ration it is important to include the value of this index in nutritive feed.…”
Section: Resultsmentioning
confidence: 99%